Low-cost options for reducing consumer health risks from farm to fork where crops are irrigated with polluted water in West Africa - Amoah, Philip; Keraita, Bernard N.; Akple, Maxwell Selase Kwasi; Drechsel, Pay; Abaidoo, Robert C.; Konradsen, Flemming (International Water Management Institute, 2011)
To identify interventions which reduce health risks of consumers where highly polluted irrigation water is used to irrigate vegetables in West Africa, scientists worked over 5 years with farmers, market traders and street food vendors in Ghana. The most promising low-cost interventions with high adoption potential were analyzed for their ability to reduce common levels of pathogens (counts of fecal coliforms and helminth eggs). The analysis showed the combination potential of various interventions, especially on-farm and during vegetable washing in line with the World Health Organization (WHO) guidelines. The tested market-based interventions were important to prevent new or additional contamination.